2021
DOI: 10.1002/jev2.12143
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicle‐derived miR‐574‐5p regulates PGE2‐biosynthesis via TLR7/8 in lung cancer

Abstract: Intercellular communication plays an essential role in lung cancer (LC). One of the major players in cell‐cell‐communication is small extracellular vesicles (sEV). SEV trigger various biological responses by transporting cellular cargo to target cells. One essential sEV component are microRNAs (miRs), whose transport has recently attracted increasing research interest. We report that prostaglandin E 2 (PGE 2 ), a key inflammatory lipid mediator, specifically induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 58 publications
1
29
1
Order By: Relevance
“…In recent years, several studies have shown that sEV from different cell types have different combinations and amounts of these proteins on their surface [ 34 , 35 ]. We supported these findings with the characterization of the sEV phenotype from non-small cell lung cancer (NSCLC) cells [ 36 ]. SEV populations of the NSCLC subtypes of adeno- and squamous cell carcinoma exhibit the distinct expression and colocalization of CD9, CD63, and CD81 at a single sEV level.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In recent years, several studies have shown that sEV from different cell types have different combinations and amounts of these proteins on their surface [ 34 , 35 ]. We supported these findings with the characterization of the sEV phenotype from non-small cell lung cancer (NSCLC) cells [ 36 ]. SEV populations of the NSCLC subtypes of adeno- and squamous cell carcinoma exhibit the distinct expression and colocalization of CD9, CD63, and CD81 at a single sEV level.…”
Section: Introductionsupporting
confidence: 57%
“…SEV populations of the NSCLC subtypes of adeno- and squamous cell carcinoma exhibit the distinct expression and colocalization of CD9, CD63, and CD81 at a single sEV level. We further demonstrated that among themselves, individual sEV populations are highly heterogeneous [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…As we mentioned above, single or combined application of RNA sensor agonists is becoming a potential effective treatment of cancers, and more burgeoning agonists have been found and developed. It is reported that even recombinant viruses and cellular noncoding RNAs are expected to be agonists [ 74 , 76 , 106 108 ]. Although the primary focus lies on RNA sensor agonists in combination with other conventional treatments or as components of cancer vaccines, systematic treatment strategies based on RNA sensors, novel drug delivery methods and innovative combination with other immunotherapies will continue to promote progress in this field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several noncoding RNAs and even recombinant virus have been identified as RNA senor inducers. MiR-574-5p derived from small extracellular vesicles activated TLR7/8, thereby decreased PGE2-levels in lung cancer [ 106 ]. CircNDUFB2 is reported to be recognized by RIG-I to activate RIG-I-MAVS signaling cascades and recruit immune cells into the TME in NSCLC [ 107 ].…”
Section: Rna Sensors In Cancer Immunotherapymentioning
confidence: 99%
“…In a previous study involving the analysis of exosomes secreted by different cell lines, some miRNA subgroups, such as miR-150, miR-142-3p and miR-451, were found to preferentially localize into exosomes ( 56 ). For instance, miRNA-574-5p has been shown to be only expressed in lung adenocarcinoma cells, but not in squamous cell carcinoma, suggesting a cell-specific response to exosomal miRNAs, which may be due to the unique composition of tetraspanin which strongly influences EV uptake ( 57 ). Exosomes internalize miRNAs through various mechanisms, and different RNA subpopulations bind to different exosome-targeted RNA-binding proteins (RBPs).…”
Section: Exosomal Micrornasmentioning
confidence: 99%